2014
DOI: 10.1167/14.6.5
|View full text |Cite
|
Sign up to set email alerts
|

Categorical membership modulates crowding: Evidence from characters

Abstract: Visual crowding is generally thought to affect recognition mostly or only at the level of feature combination. Calling this assertion into question, recent studies have shown that if a target object and its flankers belong to different categories crowding is weaker than if they belong to the same category. Nevertheless, these results can be explained in terms of featural differences between categories. The current study tests if category-level (i.e., high-level) interference in crowding occurs when featural di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 33 publications
2
33
1
Order By: Relevance
“…Interestingly, categorical aspects influence crowding, showing that crowding is not limited to low-level interactions. Reuther and Chakravarthi (2014) found better performance in conditions in which the target and the flankers belonged to a different rather than the same category. However, Chanceaux et al (2014) found that complexity predicted flanker interference better than familiarity and better than target-flanker similarity.…”
Section: Introductionmentioning
confidence: 85%
“…Interestingly, categorical aspects influence crowding, showing that crowding is not limited to low-level interactions. Reuther and Chakravarthi (2014) found better performance in conditions in which the target and the flankers belonged to a different rather than the same category. However, Chanceaux et al (2014) found that complexity predicted flanker interference better than familiarity and better than target-flanker similarity.…”
Section: Introductionmentioning
confidence: 85%
“…Although many studies of crowding have investigated how the structural difference between the target and the flankers influences the strength or extent of crowding (Bernard & Chung, 2011;Chung, Levi, & Legge, 2001;Kooi, Toet, Tripathy, & Levi, 1994;Wang, He, & Legge, 2014), only a few studies have investigated whether different categories of items could induce different types of crowding (Reuther & Chakravarthi, 2014). Based on an influential study in the field of psycholinguistics, it has been claimed that letters and symbols may trigger different crowding processes (Tydgat & Grainger, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The specific interaction of the flanker identity with the target could be the reason for more crowding with letter than bar flankers (Dakin et al, 2010). When bar rather than letter flankers are used, the bar may be less likely to change the percept of the target letter because the bars do not provide an anchor or similar feature to confuse with the target letter (Bernard & Chung, 2011), nor do they form part of a meaningful group with the target (Reuther & Chakravarthi, 2014). There is also evidence that the number of flanker features within a receptive field contributes to crowding, particularly if they are sufficiently similar to the target to be grouped with it perceptually (Bernard & Chung, 2011;Manassi, Sayim, & Herzog, 2012;Saarela, Sayim, Westheimer, & Herzog, 2009).…”
Section: Discussionmentioning
confidence: 99%